Optimalisasi Supervisi Akademik dalam Meningkatkan Kinerja guru di Sekolah Dasar Islam Terpadu Nur Inayah - Kafrina; Jummeida Zalianty; Rahma Fitra; Ilham Ageng Subekti; Muhammad Hidayat; Syafaruddin Subekti; Arrum Intan Sari (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to analyze the implementation of academic supervision, identify obstacles to optimizing academic supervision, describe efforts to optimize academic supervision, and examine its contribution to improving teacher performance at SD IT Nur Inayah Kubang. This research employed a qualitative descriptive approach. The research subjects consisted of the principal and teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation. Observations focused on the implementation of academic supervision, classroom learning activities, interactions between the principal and teachers during supervision, and changes in teacher performance following supervision. Data were analyzed through data reduction, data display, and conclusion drawing.The findings revealed that academic supervision was systematically conducted twice each semester, namely at the beginning and in the middle of the semester. The supervision activities included reviewing instructional documents, observing classroom teaching, and providing feedback to teachers. However, its implementation had not been fully optimized due to the principal’s limited time, heavy managerial workload, insufficient post-observation feedback sessions, and teachers’ perceptions of supervision as an evaluative activity. Efforts to optimize academic supervision included structured supervision planning, strengthening collaborative communication, providing constructive feedback, and conducting follow-up activities through continuous professional development programs. Academic supervision contributed positively to improving teacher performance, particularly in lesson planning, instructional implementation, and learning evaluation.